PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR MATA PELAJARAN PJOK MATERI GERAK DASAR PENCAK SILAT SEKOLAH DASAR - Andi Prastowo; Sardjijo; Bambang Ismanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Android-based learning media in PJOK subjects, especially basic pencak silat movement material in elementary schools, using the ADDIE method. In addition, this study also examines the influence of the media on student motivation and learning outcomes. This study is a Research & Development (R&D) with ADDIE stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 46 students in grades V and VI of SDN 01 Wringinagung. Validation was carried out by material experts, media experts, and language experts. Data were collected through questionnaires, tests, and observations, then analyzed qualitatively and quantitatively using validity, reliability, t-tests, and coefficients of determination. The results of the study showed that the developed learning media had a good level of feasibility. The assessment from material experts reached 75.16% (feasible), language experts 73.33% (feasible), and media experts 77.12% (feasible). The field trial obtained a score of 81.95% (very feasible). From the influence analysis, this media contributed 45.6% to the increase in learning motivation (R Square = 0.456). The t-test on learning outcomes showed a significance value of 0.000 < 0.005 with a t-count of 11.891> t-table 2.014, which means there is a significant increase in learning outcomes.